Arbeidarpartiet, bolsjevikpartiet og sovjetstaten 1917–1991 - Hallvard Tjelmeland (Arbeiderhistorie)
The article discusses the long-term effects of the Russian revolution on the Norwegian labour movement, primarily the dominant Norwegian Labour Party. This influence will be assessed from two aspects: its relationship to the Soviet Communist Party, and to the state it created. To reveal the content of and changes in the Norwegian Labour Party in relation to these two variables, it is necessary to see how this was performed in different periods. In the first period, from the Revolution until the schism within the dominant wing of the Norwegian labour movement in 1923, there was a strong degree of identification with both the Bolshevik Party and the Bolshevik State. In the period 1923-1939, there were no formal party ties. The Norwegian Labour Party defined itself to the left in the international labour movement and had an ambivalent and increasingly critical attitude to the Soviet Communist Party, but still backed the «workers’ state» in the east. During the years 1939-1955, both the Soviet state and the Soviet Communist Party were perceived as threatening entities owing in great part to the Moscow processes and power politics following the Molotov-Ribbentrop Pact. Experiences from the Second World War laid the foundation for a bridge-building approach towards the Soviet Union, and elements from this strategy were also brought into the later NATO membership. After Stalin’s death the dominant point of view of the Labour Party was that the Soviet Union was an authoritarian state that acted rationally on its own security premises, and from this there developed a tradition of critical dialogue that became hegemonic. The article specifically argues against viewpoints tending to explain elements of these bridge-building policies and critical dialogues as the result of an ideological affinity.